APLIKASI MOBILE KAMUS ISTILAH KOMPUTER BERBASIS ANDROID - Mulyana, Herlan; Maimunah, Maimunah (LPPM Universitas Islam 45 Bekasi, 2014)
ABSTRACT Dictionary on mobile phones is more practical than conventional dictionaries, because at the moment the user needs a lot of information quickly anywhere without any time restrictions. In addition to the dictionary is able to provide information dictionary can also be used as a container for learning. In scientific writing, the author makes an application using the Android Dictionary of Computer Terms. The author of Android in the making of this application for android based on open source. The design of this application is made by xml code in Eclipse, the Android Java as a programming language and SQLite as database creation. Dictionary of Computer Terms is created because of the need for information is very important and a difficult time if you have to search for the meaning of the word or term using conventional dictionaries. It is expected that with this dictionary the user can search for a computer terms with access directly from their mobile phones without having to look for in conventional dictionaries. Keyword: application,dictionary,computer term , android, eclipse ABSTRAK Kamus pada telepon selular lebih praktis dibandingkan dengan kamus cetak konvensional, karena pada saat ini pengguna membutuhkan banyak informasi dengan cepat dimana saja tanpa adanya batasan waktu. Selain kamus mampu memberikan informasi kamus juga dapat dijadikan wadah untuk belajar. Dalam penulisan ilmiah ini penulis membuat sebuah aplikasi Kamus Istilah Komputer menggunakan Android. Penulis mengangkat Android dalam pembuatan aplikasi ini karena android berbasis open source. Perancangan aplikasi ini dibuat dengan kode xml pada Eclipse, Java Android sebagai bahasa pemrograman dan SQLite sebagai pembuatan database. Kamus Istilah Komputer ini dibuat karena kebutuhan akan informasi sangat penting serta waktu yang sulit jika harus mencari arti kata ataupun istilah menggunakan kamus cetak konvensional. Diharapkan dengan kamus ini pengguna dapat mencari pengertian istilah komputer dengan mengakses langsung dari telepon selular mereka tanpa harus mencari pada kamus cetak konvensional. Kata Kunci : aplikasi, kamus, istilah komputer, android, eclipse.